Primary Closure Consideration and Local Flap Reconstruction in a Neonate with Giant Occipital Meningoencephalocele: A Case Report and Technical Considerations - Anggia, Risa; Hidayat, Imam; Rizal, Syamsul (Journal of Society Medicine, 2026)
Introduction: Meningoencephalocele is a rare congenital neural tube defect characterized by herniation of meninges and brain tissue through a cranial defect. Giant occipital lesions in neonates present substantial neurosurgical and reconstructive challenges owing to fragile tissues, limited physiological reserve, and increased risk of cerebrospinal fluid (CSF) leakage, wound complications, and infection. Despite well-established neurosurgical principles, optimal strategies for soft tissue reconstruction in this population remain insufficiently reported. Case Description: An 11-day-old female neonate presented with a large midline occipital mass that had been present since birth. Clinical examination revealed a soft, fluctuant, skin-covered lesion without neurological deficits or signs of infection. Cranial imaging revealed an occipital skull defect with herniation of the meninges and brain tissue, consistent with occipital meningoencephalocele. Following a multidisciplinary evaluation, primary closure was considered but deemed unsafe because of excessive tension. Therefore, staged surgical management was performed. Neurosurgical excision of the non-functional herniated tissue and watertight dural repair was followed by tension-free scalp reconstruction using a local occipital rotation flap. The post-excisional defect measured approximately 8 × 6 cm, and the total operative time was approximately 180 minutes. No intraoperative complications occurred. The postoperative course was uneventful, with stable wound healing, intact flap viability, and no evidence of CSF leakage, wound dehiscence, infection, or neurological deterioration during the early follow-up. Conclusion: A staged multidisciplinary approach integrating precise neurosurgical repair with well-planned local flap reconstruction enables safe closure, preserves neural protection, minimizes complications, and provides favorable functional and aesthetic outcomes in neonatal occipital meningoencephalocele.